Lithium battery silicon-carbon composite negative electrode material and preparation method and application thereof

By using porous carbon matrix to deposit silica graphene composite material in the negative electrode material of lithium-ion batteries, the problems of electrode fracture and instability during lithiation deliquification are solved, and higher battery stability and cycling performance are achieved.

CN119447211APending Publication Date: 2025-02-14LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310986150.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The volume effect of the negative electrode materials of existing lithium-ion batteries leads to electrode rupture and unstable SEI films during the deliquification process of existing lithium-ion batteries has not been effectively solved, which limits the development of the battery.

Method used

By depositing the silicon graphene composite in the pores of porous carbon, sufficient voids are provided to buffer the volume expansion of the silicon particles and a three-dimensional conductive network is constructed to improve the conductivity of the active substance.

Benefits of technology

Improves the stability and cycling performance of the electrode, and enhances the first-week efficiency and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447211A_ABST
    Figure CN119447211A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a lithium battery silicon-carbon composite negative electrode material and a preparation method and application thereof. The lithium battery silicon-carbon composite negative electrode material comprises a porous carbon matrix, nano silicon particles and few-layer graphene, the porous carbon is used as a matrix of the silicon-carbon composite negative electrode material, and the nano silicon particles are uniformly distributed on the surface and between layers of the few-layer graphene sheet in an atomic-scale form to form a silicon-graphene composite material which is deposited in pores of the porous carbon; wherein the particle size of the nano silicon particles ranges from 0.1 nm to 50 nm; the thickness of the few-layer graphene sheets is 0.3-2.0 nm, the size of the sheets is 10-100 nm, and the number of the layers is larger than or equal to 1 and smaller than or equal to 5; and the pore diameter of pores of the porous carbon matrix is between 0.1 nm and 500 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium battery silicon-carbon composite negative electrode material and a preparation method and application thereof. Background Art

[0002] In the past 20 years, lithium-ion batteries have been widely used due to their advantages in energy density and cycle life, becoming the mainstream power source for small electronic devices. However, with the development of electric vehicles and electric devices, higher requirements are placed on the performance of lithium-ion batteries (LIBs), especially their battery capacity and energy density. It is urgent to design the next generation of LIBs with higher power capacity and better cycle performance.

[0003] As one of the important components of lithium-ion batteries, it is essential to improve the performance of negative electrode materials. Carbon has become the most popular and widely used negative electrode material for commercial batteries due to its stable cycle characteristics, but its relatively small charge storage capacity (372mAh / g) has severely limited the development of LIBs. Silicon has a high charge storage capacity (about 372mAh / g) due to its low charge storage capacity (about 372mAh / g) when fully lithiated to form Li 22 Si5 exhibits a storage capacity of up to 4200 mA h / g (10 times that of graphite) and a relatively low working potential (relative to Li / Li + The average value is about 0.4V), and its high abundance in the earth's crust and environmental friendliness make it one of the most promising candidates for the next generation of lithium battery negative electrodes to replace graphite electrodes.

[0004] However, due to the huge volume effect of silicon during the lithiation and delithiation process, and the resulting problems such as electrode rupture and unstable SEI film have not been effectively solved, the preparation of silicon-carbon composite materials by combining high-capacity silicon materials with high-stability carbon materials has become the focus of current attention. Summary of the invention

[0005] The purpose of the present invention is to provide a lithium battery silicon-carbon composite negative electrode material and its preparation method and application. Through the structure of depositing silicon-graphene composite materials in the pores of porous carbon, sufficient gaps are set around silicon particles to provide buffer space for the volume expansion of silicon particles during the cycle process, thereby increasing the stability of the electrode. The three-dimensional conductive network constructed by the silicon-graphene composite material and porous carbon not only improves the conductivity of the active material but also increases the first cycle efficiency and cycle performance of the electrode.

[0006] To this end, in a first aspect, an embodiment of the present invention provides a lithium battery silicon-carbon composite negative electrode material, comprising: a porous carbon matrix, nano-silicon particles, and few-layer graphene;

[0007] The porous carbon is used as the matrix of the silicon-carbon composite negative electrode material, and the nano-silicon particles are evenly distributed on the surface and between the layers of the few-layer graphene sheets in an atomic form to form a silicon-graphene composite material, which is deposited in the pores of the porous carbon;

[0008] Among them, the particle size of the nano-silicon particles is 0.1nm-50nm; the thickness of the few-layer graphene flakes is 0.3nm-2.0nm, the flake size is 10nm-100nm, the number of layers is greater than or equal to 1 layer and less than or equal to 5 layers; the pore size of the pores of the porous carbon matrix is ​​between 0.1nm-500nm.

[0009] Preferably, the lithium battery silicon-carbon composite negative electrode material further comprises a carbon coating layer, and the carbon coating layer is coated on the porous carbon matrix on which the silicon-graphene composite material is deposited.

[0010] Preferably, in the porous carbon matrix deposited with the silicon-graphene composite material, the mass fraction of the silicon nanomaterial is 0.1-70%, and the mass fraction of the carbon material is 30%-95%;

[0011] In the silicon-carbon composite material, the mass fraction of the carbon coating layer in the silicon-carbon composite material is 0-20%.

[0012] In a second aspect, an embodiment of the present invention provides a method for preparing the lithium battery silicon-carbon composite negative electrode material according to the first aspect, comprising:

[0013] Step 1: introducing a protective gas into a plasma reaction chamber of a plasma vapor deposition collection device, exhausting the air in the chamber, and making the plasma reaction chamber reach a vacuum or negative pressure state;

[0014] Step 2: Place the porous carbon as a reaction substrate into the collection area of ​​the plasma vapor deposition collection device, start the plasma generator, and after the arc discharge of the system is stable, pass the silicon source material and the carbon source material into the high temperature zone of the plasma torch in the plasma reaction chamber for reaction. The reaction product is carried away from the high temperature zone of the plasma torch by the working gas and enters the collection area, where it condenses, crystallizes and nucleates to obtain a silicon-graphene composite material, which is deposited in the pores of the porous carbon to form a silicon-carbon composite negative electrode material for lithium batteries.

[0015] Preferably, the protective gas is a mixture of one or more of nitrogen, argon, helium and neon;

[0016] The working gas is a mixture of one or more of nitrogen, argon, helium and neon.

[0017] Preferably, the silicon source material is in a solid or gaseous state, and specifically includes one or more of silicon powder, monosilane, disilane, methylsilane, tetrafluorosilane, dichlorosilane, and trichlorosilane;

[0018] The carbon source material is in the form of solid powder or gas, and specifically includes: one or more of glucose, starch, citric acid, carbon black, graphite, carbon nanohorns, carbon nanotubes, graphene, carbon fibers and biochar, or one or more of methane, ethane, ethylene, acetylene, propane, propylene and propyne.

[0019] Preferably, the preparation method further comprises: carbon coating the porous carbon deposited with the silicon-graphene composite material; the carbon coating method comprises: at least one of gas phase coating, liquid phase coating or solid phase coating.

[0020] In a third aspect, an embodiment of the present invention provides a negative electrode, comprising the lithium battery silicon-carbon composite negative electrode material described in the first aspect above.

[0021] In a fourth aspect, an embodiment of the present invention provides a lithium battery, comprising the negative electrode described in the third aspect above.

[0022] The lithium battery silicon-carbon composite negative electrode material provided by the embodiment of the present invention has a structure in which a silicon-graphene composite material is deposited in the pores of porous carbon, and sufficient gaps are set around the silicon particles to provide a buffer space for the volume expansion of the silicon particles during the cycle, thereby increasing the stability of the electrode. The three-dimensional conductive network constructed by the silicon-graphene composite material and porous carbon not only improves the conductivity of the active material but also increases the first-cycle efficiency and cycle performance of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Flow chart of the method for preparing the silicon-carbon composite negative electrode material for a lithium battery provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0025] The embodiment of the present invention provides a lithium battery silicon-carbon composite negative electrode material, comprising: a porous carbon matrix, nano silicon particles, and few-layer graphene;

[0026] Porous carbon is used as the matrix of the silicon-carbon composite negative electrode material. Nano-silicon particles are evenly distributed on the surface and between the few-layer graphene sheets at the atomic level to form a silicon-graphene composite material, which is deposited in the pores of the porous carbon.

[0027] Among them, the particle size of nano-silicon particles is 0.1nm-50nm; the thickness of the few-layer graphene flakes is 0.3nm-2.0nm, the size of the flakes is 10nm-100nm, the number of layers is greater than or equal to 1 layer and less than or equal to 5 layers; the pore size of the pores of the porous carbon matrix is ​​between 0.1nm-500nm.

[0028] Among them, the lithium battery silicon-carbon composite negative electrode material preferably also includes a carbon coating layer, and the carbon coating layer is coated on the porous carbon matrix deposited with the silicon-graphene composite material.

[0029] In the porous carbon matrix deposited with the silicon-graphene composite material, the mass fraction of silicon nanomaterials is 0.1-70%, and the mass fraction of carbon materials is 30%-95%; in the silicon-carbon composite material, the mass fraction of the carbon coating layer is 0-20% of the silicon-carbon composite material.

[0030] The above-mentioned lithium battery silicon-carbon composite negative electrode material of the present invention can be obtained through the following preparation method steps.

[0031] Step 110, introducing a protective gas into a plasma reaction chamber of a plasma vapor deposition collection device, exhausting the air in the chamber, and making the plasma reaction chamber reach a vacuum or negative pressure state;

[0032] Step 120, placing the porous carbon as a reaction substrate into the collection area of ​​the plasma vapor deposition collection device, starting the plasma generator, and after the arc discharge of the system is stable, passing the silicon source material and the carbon source material into the high temperature zone of the plasma torch in the plasma reaction chamber for reaction, and the reaction product is carried away from the high temperature zone of the plasma torch by the working gas and enters the collection area, condenses, crystallizes and nucleates to obtain a silicon-graphene composite material, which is deposited in the pores of the porous carbon to form a silicon-carbon composite negative electrode material for lithium batteries.

[0033] After the reaction is completed, turn off the gas source and power supply, wait for natural cooling and take out the material. The composite reaction occurs at the atomic level, which is faster and more efficient. The mass proportion of silicon in the silicon-graphene composite material is 0.1-70%.

[0034] Furthermore, the obtained material sample is placed in a vacuum drying oven and dried at a temperature of 60-80° C. for 6-12 hours.

[0035] Afterwards, the porous carbon on which the silicon-graphene composite material is deposited may be carbon coated to obtain the final lithium battery silicon-carbon composite negative electrode material. The carbon coating method may include: at least one of gas phase coating, liquid phase coating or solid phase coating.

[0036] In the above steps, the protective gas is a mixture of one or more of nitrogen, argon, helium and neon; and the working gas is a mixture of one or more of nitrogen, argon, helium and neon.

[0037] The silicon source material is in a solid or gaseous state, and specifically includes one or more of silicon powder, monosilane, disilane, methylsilane, tetrafluorosilane, dichlorosilane, and trichlorosilane;

[0038] The carbon source material is in the form of solid powder or gas, and specifically includes: one or more of glucose, starch, citric acid, carbon black, graphite, carbon nanohorns, carbon nanotubes, graphene, carbon fibers and biochar, or one or more of methane, ethane, ethylene, acetylene, propane, propylene and propyne.

[0039] The silicon-carbon composite negative electrode material provided in the embodiment of the present invention generates a silicon-graphene composite structure by a plasma gas phase method. The nanoscale and high stability of the few-layer graphene carbon material itself and the three-dimensional conductive network formed between the layers of the structure reserve sufficient buffer space for the expansion of silicon, thereby maintaining the integrity of the electrode structure, while improving the electronic conductivity, battery rate performance and cycle performance of the material.

[0040] The lithium battery silicon-carbon composite negative electrode material obtained above can be used for preparing the negative electrode of the lithium battery.

[0041] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the silicon-carbon composite negative electrode material for lithium batteries of the present invention are respectively described in the following with multiple specific examples. The plasma reaction device used in the following embodiments is a thermal plasma metallurgical reaction device, model JCL-L70.

[0042] Example 1

[0043] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0044] (1) Argon gas is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in the collection area of ​​a plasma vapor deposition device at room temperature;

[0045] (2) Start the plasma reaction device. After the arc discharge temperature of the system rises to 2500K, switch the argon gas to a CH4 / Ar mixed gas with a methane content of 20% by volume, and 50 Silicon powder (purity 99%) of about 15 μm is radially fed into the plasma torch through a powder feeder through a mixed gas carrier gas. The plasma generator operates at a constant power. Due to the high enthalpy of the hot plasma, the raw material is completely evaporated. The silicon vapor is then transported to the reaction chamber with the plasma flow, and a countercurrent Ar gas is injected into the reaction chamber to increase the quenching rate of the formation of nanoparticles. Due to the large temperature gradient, the silicon vapor nucleates and condenses in the plasma tail collection area. Natural cooling to room temperature obtains porous carbon deposited with silicon-graphene composite materials.

[0046] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and cooling to room temperature to obtain a silicon-carbon composite negative electrode material containing a carbon coating layer.

[0047] Example 2

[0048] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0049] (1) Argon gas is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in the collection area of ​​a plasma vapor deposition device at room temperature;

[0050] (2) Start the plasma reaction device. After the arc discharge temperature of the system rises to 2000K, switch the argon gas to a CH4 / Ar mixed gas with a methane content of 20% by volume, and 50 Silicon powder (purity 99%) of about 15 μm is radially fed into the plasma torch through a powder feeder through a mixed gas carrier. The plasma generator operates at a constant power. Due to the high enthalpy of the hot plasma, the raw material is completely evaporated. The silicon vapor is then transported to the reaction chamber with the plasma flow, and a countercurrent Ar gas is injected into the reaction chamber to increase the quenching rate of the formation of nanoparticles. Due to the large temperature gradient, the silicon vapor nucleates and condenses in the plasma tail collection area. Natural cooling to room temperature obtains porous carbon deposited with silicon-graphene composite materials.

[0051] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and cooling to room temperature to obtain a silicon-carbon composite negative electrode material containing a carbon coating layer.

[0052] Example 3

[0053] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0054] (1) Argon gas is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in the collection area of ​​a plasma vapor deposition device at room temperature;

[0055] (2) Start the plasma reaction device. After the arc discharge temperature of the system rises to 3000K, switch the argon gas to a CH4 / Ar mixed gas with a methane content of 20% by volume, and50 Silicon powder (purity 99%) of about 5 μm is radially fed into the plasma torch through a powder feeder through a mixed gas carrier. The plasma generator operates at a constant power. Due to the high enthalpy of the hot plasma, the raw material is completely evaporated. The silicon vapor is then transported to the reaction chamber with the plasma flow, and a countercurrent Ar gas is injected into the reaction chamber to increase the quenching rate of the formation of nanoparticles. Due to the large temperature gradient, the silicon vapor nucleates and condenses in the plasma tail collection area. Natural cooling to room temperature obtains porous carbon deposited by silicon-graphene composite materials.

[0056] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and naturally cooling it to room temperature to obtain a silicon-carbon composite negative electrode material containing a carbon coating layer.

[0057] Example 4

[0058] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0059] (1) Add silicon powder and graphite powder in a mass ratio of 3:7 into a mixer, and add a certain amount of anhydrous ethanol to mix and stir. After the mixed raw materials are vacuum dried, they are ground into powder and sieved to obtain D 50 =15μm silicon-carbon mixed powder;

[0060] (2) nitrogen is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in a collection area of ​​a plasma vapor deposition device at room temperature;

[0061] (3) Start the plasma reaction device. After the arc discharge of the system is stable, the silicon-carbon mixed powder is carried by the N2 carrier gas radially through the powder feeder and fed into the plasma torch. The plasma generator operates at a constant power. Due to the high enthalpy of the thermal plasma, the raw material is completely evaporated. The silicon vapor is then transported to the reaction chamber with the plasma flow, and a countercurrent N2 gas is injected into the reaction chamber to increase the quenching rate of the formation of nanoparticles. Due to the large temperature gradient, the silicon vapor nucleates and condenses in the plasma tail collection area. Naturally cool to room temperature to obtain a silicon-graphene composite material;

[0062] (4) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (3) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and cooling to room temperature to obtain a negative electrode material containing a carbon coating layer.

[0063] Example 5

[0064] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0065] (1) Add silicon powder and graphite powder in a mass ratio of 1:1 into a mixer, and add a certain amount of anhydrous ethanol to mix and stir. After the mixed raw materials are vacuum dried, they are ground into powder and sieved to obtain D 50 =15μm silicon-carbon mixed powder;

[0066] (2) nitrogen is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in a collection area of ​​a plasma vapor deposition device at room temperature;

[0067] (3) Start the plasma reaction device. After the arc discharge of the system is stable, the silicon-carbon mixed powder is carried by the N2 carrier gas radially through the powder feeder and fed into the plasma torch. The plasma generator operates at a constant power. Due to the high enthalpy of the hot plasma, the raw material is completely evaporated. The silicon vapor is then transported to the reaction chamber with the plasma flow, and the countercurrent N2 gas is injected into the reaction chamber to increase the quenching rate of the formation of nanoparticles. Due to the large temperature gradient, the silicon vapor nucleates and condenses in the plasma tail collection area. Naturally cool to room temperature to obtain porous carbon deposited with silicon-graphene composite materials.

[0068] (4) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (3) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and naturally cooling to room temperature to obtain porous carbon deposited by silicon-graphene composite material.

[0069] Example 6

[0070] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0071] (1) nitrogen is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in a collection area of ​​a plasma vapor deposition device at room temperature;

[0072] (2) Start the plasma reaction device. After the arc discharge temperature of the system rises to 2500K, switch the nitrogen gas to a C2H2 / N2 mixed gas with 20% acetylene content and 50Silicon powder (purity 99%) of about 15 μm is radially fed into the plasma torch through a powder feeder through a mixed gas carrier. The plasma generator operates at a constant power. Due to the high enthalpy of the hot plasma, the raw material is completely evaporated. The silicon vapor is then transported to the reaction chamber with the plasma flow, and a countercurrent Ar gas is injected into the reaction chamber to increase the quenching rate of the formation of nanoparticles. Due to the large temperature gradient, the silicon vapor nucleates and condenses in the plasma tail collection area. Natural cooling to room temperature obtains porous carbon deposited with silicon-graphene composite materials.

[0073] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and cooling to room temperature to obtain a negative electrode material containing a carbon coating layer.

[0074] Example 7

[0075] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0076] (1) nitrogen is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in a collection area of ​​a plasma vapor deposition device at room temperature;

[0077] (2) Start the plasma reaction device. After the arc discharge temperature of the system rises to 3000K, switch the nitrogen gas to a C2H2 / N2 mixed gas with 20% acetylene content and 50 Silicon powder (purity 99%) of about 15 μm is radially fed into the plasma torch through a powder feeder through a mixed gas carrier. The plasma generator operates at a constant power. Due to the high enthalpy of the hot plasma, the raw material is completely evaporated. The silicon vapor is then transported to the reaction chamber with the plasma flow, and a countercurrent N2 gas is injected into the reaction chamber to increase the quenching rate of the formation of nanoparticles. Due to the large temperature gradient, the silicon vapor nucleates and condenses in the plasma tail collection area. Naturally cool to room temperature to obtain porous carbon deposited by silicon-graphene composite materials.

[0078] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and cooling to room temperature to obtain a negative electrode material containing a carbon coating layer.

[0079] Example 8

[0080] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0081] (1) Argon gas is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in the collection area of ​​a plasma vapor deposition device at room temperature;

[0082] (2) Start the plasma reaction device, and after the arc discharge stable temperature of the system rises to 2500K, switch the argon gas to a CH4 / Ar mixed gas with a methane volume content of 20% as a carbon source, and introduce the silicon source SiH4 into the plasma furnace chamber for chemical vapor deposition. Cool naturally to room temperature to obtain porous carbon deposited by silicon-graphene composite materials.

[0083] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and naturally cooling to room temperature to obtain porous carbon deposited by silicon-graphene composite material.

[0084] Example 9

[0085] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0086] (1) Argon gas is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in the collection area of ​​a plasma vapor deposition device at room temperature;

[0087] (2) Start the plasma reaction device, and after the arc discharge stable temperature of the system rises to 2500K, switch the argon gas to a CH4 / Ar mixed gas with a methane volume content of 20% as a carbon source, and introduce the silicon source CH3SiH3 into the plasma furnace chamber for chemical vapor deposition. Naturally cool to room temperature to obtain porous carbon deposited by silicon-graphene composite materials.

[0088] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and cooling to room temperature to obtain a negative electrode material containing a carbon coating layer.

[0089] Example 10

[0090] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0091] (1) nitrogen is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in a collection area of ​​a plasma vapor deposition device at room temperature;

[0092] (2) Start the plasma reaction device, and after the arc discharge stable temperature of the system rises to 2500K, switch the nitrogen gas to a C2H2 / N2 mixed gas with 20% acetylene as the carbon source, and introduce the silicon source SiH4 into the plasma furnace chamber for chemical vapor deposition. Cool naturally to room temperature to obtain porous carbon deposited by silicon-graphene composite material.

[0093] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and cooling to room temperature to obtain a negative electrode material containing a carbon coating layer.

[0094] Embodiment 11

[0095] This embodiment provides a method for preparing a silicon-carbon composite material, and the specific process is as follows:

[0096] (1) nitrogen is introduced into the plasma reaction chamber as a protective atmosphere to exhaust the air in the chamber to achieve a vacuum state, and the porous carbon substrate is placed in a collection area of ​​a plasma vapor deposition device at room temperature;

[0097] (2) Start the plasma reaction device, and after the arc discharge stable temperature of the system rises to 2500K, switch the nitrogen gas to a C2H2 / N2 mixed gas with 20% acetylene as the carbon source, and introduce the silicon source CH3SiH3 into the plasma furnace chamber for chemical vapor deposition. Cool naturally to room temperature to obtain porous carbon deposited by silicon-graphene composite material.

[0098] (3) performing gas-phase carbon coating on the prepared negative electrode material, specifically: placing the material obtained in step (2) in a tubular furnace, heating it to 800° C. under a protective atmosphere, then switching to a mixed gas of argon and acetylene in a volume ratio of 1:1 for gas-phase coating, heating at 800° C. for 2 h, then turning off the organic gas source, and cooling to room temperature to obtain a negative electrode material containing a carbon coating layer.

[0099] The negative electrode materials obtained in the above-mentioned embodiments were used for battery assembly and testing.

[0100] In order to test its electrochemical performance, the silicon-carbon composite negative electrode material containing a carbon coating layer prepared in each embodiment is used as an active material, and the mass ratio of active material: conductive carbon black (SP): polyvinylidene fluoride (PVDF) = 90.0:5.0:5.0 is used as an example. The total amount of the three is 15g. Add 0.75g PVDF to 24.25g N-methylpyrrolidone (NMP), the speed of the dispersion disk is 2000r / min, and disperse for 30min until the glue is clear. Add 0.75g SP to the glue, the speed of the dispersion disk is 2000r / min, and disperse for 40min. Add 13.5g of active material to the slurry, the speed of the dispersion disk is 2000r / min, disperse for 40min, and add an appropriate amount of NMP to adjust the viscosity to 1000-3000mPa.s. Sieve the slurry with a 180-mesh screen before coating. The slurry was coated on copper foil respectively, and the coated electrode was dried at 110°C. After drying, it was cut into circular electrode pieces with a diameter of 8 mm. Under vacuum conditions, the electrode pieces were dried at 120°C for 6 hours and then transferred to a glove box for standby use. The assembly of the simulated battery was carried out in a glove box with an Ar atmosphere. Metal lithium was used as the counter electrode, and 1 mol of LiPF6 was dissolved in 1L of ethylene carbonate and diethyl carbonate solution with a volume ratio of 1:1 as the electrolyte to prepare a lithium-ion button battery. Its structure and electrochemical performance were evaluated by testing.

[0101] In order to verify the cycle stability of the electrode structure of the silicon-carbon composite negative electrode material, the button cell after 100 electrochemical cycles was removed from the negative electrode sheet in a glove box with Ar atmosphere, and the change in the cross-sectional thickness of the electrode sheet was measured. The expansion rate of the electrode sheet was obtained by comparing it with the initial thickness of the electrode.

[0102]

[0103]

[0104] Table 1

[0105] It can be seen that the silicon-carbon composite negative electrode material prepared by the present invention has excellent cycle capacity retention rate and low expansion rate.

[0106] The silicon-carbon composite negative electrode material provided in the embodiment of the present invention generates a silicon-graphene composite structure by a plasma gas phase method. The nanoscale and high stability of the few-layer graphene carbon material itself and the three-dimensional conductive network formed between the layers of the structure reserve sufficient buffer space for the expansion of silicon, thereby maintaining the integrity of the electrode structure, while improving the electronic conductivity, battery rate performance and cycle performance of the material.

[0107] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A lithium battery silicon-carbon composite negative electrode material, characterized in that: The lithium battery silicon-carbon composite negative electrode material comprises: a porous carbon matrix, nano silicon particles, and few-layer graphene; The porous carbon is used as the matrix of the silicon-carbon composite negative electrode material, and the nano-silicon particles are evenly distributed on the surface and between the layers of the few-layer graphene sheets in an atomic form to form a silicon-graphene composite material, which is deposited in the pores of the porous carbon; Among them, the particle size of the nano-silicon particles is 0.1nm-50nm; the thickness of the few-layer graphene flakes is 0.3nm-2.0nm, the flake size is 10nm-100nm, the number of layers is greater than or equal to 1 layer and less than or equal to 5 layers; the pore size of the pores of the porous carbon matrix is ​​between 0.1nm-500nm.

2. The silicon-carbon composite material according to claim 1, characterized in that: The lithium battery silicon-carbon composite negative electrode material further comprises a carbon coating layer, and the carbon coating layer is coated on the porous carbon substrate on which the silicon-graphene composite material is deposited.

3. The silicon-carbon composite material according to claim 2, characterized in that: In the porous carbon matrix deposited with the silicon-graphene composite material, the mass fraction of the silicon nanomaterial is 0.1-70%, and the mass fraction of the carbon material is 30%-95%; In the silicon-carbon composite material, the mass fraction of the carbon coating layer in the silicon-carbon composite material is 0-20%.

4. A method for preparing the lithium battery silicon-carbon composite negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step 1: introducing a protective gas into a plasma reaction chamber of a plasma vapor deposition collection device, exhausting the air in the chamber, and making the plasma reaction chamber reach a vacuum or negative pressure state; Step 2: Place the porous carbon as a reaction substrate into the collection area of ​​the plasma vapor deposition collection device, start the plasma generator, and after the arc discharge of the system is stable, pass the silicon source material and the carbon source material into the high temperature zone of the plasma torch in the plasma reaction chamber for reaction. The reaction product is carried away from the high temperature zone of the plasma torch by the working gas and enters the collection area, where it condenses, crystallizes and nucleates to obtain a silicon-graphene composite material, which is deposited in the pores of the porous carbon to form a silicon-carbon composite negative electrode material for lithium batteries.

5. The preparation method according to claim 4, characterized in that: The protective gas is a mixture of one or more of nitrogen, argon, helium and neon; The working gas is a mixture of one or more of nitrogen, argon, helium and neon.

6. The preparation method according to claim 4, characterized in that: The silicon source material is in a solid or gaseous state, and specifically includes one or more of silicon powder, monosilane, disilane, methylsilane, tetrafluorosilane, dichlorosilane, and trichlorosilane; The carbon source material is in the form of solid powder or gas, and specifically includes: one or more of glucose, starch, citric acid, carbon black, graphite, carbon nanohorns, carbon nanotubes, graphene, carbon fibers and biochar, or one or more of methane, ethane, ethylene, acetylene, propane, propylene and propyne.

7. The preparation method according to claim 4, characterized in that: The preparation method further comprises: carbon coating the porous carbon deposited with the silicon-graphene composite material; the carbon coating method comprises: at least one of gas phase coating, liquid phase coating or solid phase coating.

8. A negative electrode, characterized in that The negative electrode comprises the lithium battery silicon-carbon composite negative electrode material as described in any one of claims 1 to 3.

9. A lithium battery, characterized in that: The lithium battery comprises the negative electrode as claimed in claim 8.

Citation Information

Cited By

  • Preparation method of nano silicon, nano silicon oxide and silicon-carbon nano composite material

    CN120757117A